Characterization of Follicular Atresia Responsive to BPA in Zebrafish by Morphometric Analysis of Follicular Stage Progression - M. Migliaccio; T. Chioccarelli; C. Ambrosino; A. Suglia; F. Manfrevola; O. Carnevali; S. Fasano; R. Pierantoni; G. Cobellis (International Journal of Endocrinology)
Bisphenol A is an industrial chemical compound, pervasively polluting the environment and diet, classified as an endocrine disruptor because of its interference effects on the endocrine system. In zebrafish, BPA exposure induces follicular atresia. To acquire knowledge on this atretic effect, using a qualitative and quantitative histomorphological approach, we studied zebrafish ovarian follicular stage development in response to low BPA concentrations. Results show that BPA interferes with follicular progression by affecting the previtellogenic and vitellogenic phases. In particular, BPA exposure (i) increases follicular recruitment by acting on primary stage follicles, (ii) forces the follicular transition from stage III to stage IV producing enlarged stage IV follicles, and (iii) induces atresia by producing atretic follicles that are peculiarly enlarged (i.e., big atretic follicles). We suggest that BPA induces atresia by the primary effect on recruitment of stage I follicles. This forces follicular progression and produces stage IV follicles that are peculiarly enlarged that undertake the atretic development.